Addressing holistic healthcare needs of oncology patients: Implementation and evaluation of a complementary and alternative medicine (CAM) course within an elective module designed for healthcare professionals. (December 2016) - Klafke, Nadja; Homberg, Angelika; Glassen, Katharina; Mahler, Cornelia
Abstract: Background: Patients, and especially oncology patients, increasingly demand information and application of complementary therapies to supplement their conventional medical treatment and follow-up care. Due to the widespread interest in holistic treatment opportunities in oncology populations, healthcare professionals need to be prepared in differentiating evidence-based methods of the complementary and alternative medicine (CAM) spectrum and how to consult with patients about it. Objective: This paper reports on the implementation and evaluation of a newly designed module "Complementary and Alternative Medicine in oncological healthcare" in the bachelor degree program Interprofessional Health Care (B.Sc.). Design: The study applied a developed evaluation questionnaire to capture students' perspectives on the CAM contents. This assessment instrument was administered pre and post the CAM teaching unit. Setting: Interprofessional medical education, University Hospital Heidelberg, Germany. Results: The integration of the CAM elective module was possible and was met by positive response. Students' interest was reflected in an increase of their self-reported knowledge gain and positive CAM attitude. Comparison of pre and post evaluation data demonstrate that, particularly, students' expectations on developing their own opinion about CAM, and getting an overview of the evidence-base of different CAM methods have been met. Conclusions: Evaluation results indicate that the module content was in line with the students' expectations and may have positively impacted on their general CAM attitude. The results support us in continuing to offer this CAM course within the elective module to prepare today's healthcare professionals for patient-oriented healthcare delivery.